Employee Satisfaction in Public Sector Universities: A Study in Telangana State - Banoth, Deepa; Samunnatha, V. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research investigates the level of satisfaction among teaching and non-teaching personnel in Telangana State’s public universities. Two hundred respondents, from various age categories and permanent, contractual, outsourced, and timescale employees, participated. The goals were to assess satisfaction levels and determine any disparities between age groups and occupational categories. The results show a reasonable degree of employee happiness but also point to serious flaws in organizational procedures and measurement accuracy. The study emphasizes how important it is for organizations to emphasize organized professional development opportunities and improve the validity of evaluation instruments used for organizational development and employee feedback.